The Correlation between Oxidative Stress and Asthma Control Test in Iraqi Asthmatic Patients - Yousif Nadhim Abbas; Mustafa Taha Mohammed; Nisred K. Klichkhanov (Al-Mustansiriyah Journal of Science)
Background: Asthma is a chronic disease of the airway tract, which can be triggered due to inflammatory and non-inflammatory events. Recently, the prevalence of asthma has reached a significant rate globally. Asthmatic patients have shown significant disturbance in the redox balance, resulting in oxidative stress. Objective: We have aimed to discover the relationship between the severity of asthma and oxidative stress by evaluating several indicators of oxidative stress in asthmatic patients with different degrees of control. Methods: 60 diagnosed patients with asthma were enrolled in this study in the overweight category and age range from 18 to 60 years old. Results: The levels of malondialdehyde (MDA), total oxidant status (TOS), and oxidative stress index (OSI) were observed to be significantly higher in asthmatic patients. Moreover, patients with poor asthma control have shown the highest levels of MDA, TOS, and OSI compared to those with good and moderate control of the disease. On the contrary, asthmatic patients have shown significantly lower levels of total antioxidant capacity (TAC) compared to control, where the lowest levels of TAC were observed in poor controlled asthmatic patients compared to those with good and moderate control of the disease. Additionally, a correlation between MDA, TOS, OSI, and the asthma control test (ACT) was observed in an inversely manner, while TAC and ACT were correlated in a positively manner. Conclusions: Oxidative stress has shown significant involvement in the progression of asthma.